Aktivitas pada Grand Surabaya Hotel dalam Menjalin Hubungan Baik dengan Pelanggan: (Studi Kasus Hotel Grand Surabaya) - Arinanda, Rizka Maulidia; Sadiqin, Amin (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
This study aims to determine the good relationship with customers at Grand Surabaya Hotel. The object of research is Grand Surabaya Hotel. The population of this study was in the marketing department. This study aims to determine the extent to which grand Surabaya hotel establishes good relations with its customers, the role of employees who work in the service sector fully holds tightly to the ethics and morals of the hotel in improving the quality of service at Grand Surabaya Hotel. This research method is carried out using qualitative methods in the form of information related to the problem being studied and descriptive analysis which explains clearly about related topics and data obtained through observation. The results showed that it is important to establish good relationships in all departments in service services to maintain the quality of service to guests and also operations that run well. The next research that is interesting to be developed as research is professional ethics in the hotel industry.